Hyperoodon planifrons Flower 1882 - James G. Mead; Robert L. Brownell, Jr. (Smithsonian Institution Press, 1993)
Hyperoodon planifrons Flower, 1882. Proc. Zool. Soc. Lond., 1882:392, figs. 1, 2. TYPE LOCALITY: "found upon the sea-beach of Lewis Island in the Dampier Archipelago, North-western Australia." DISTRIBUTION: Southern Hemisphere: circumpolar, antarctic to temperate waters, occasionally into tropical waters. May occur in the W North Pacific. STATUS: CITES - Appendix I. SYNONYMS: burmeisterei. COMMENTS: Reviewed by J. G. Mead (1989b). Moore (1968) erected the subgenus Frasercetus for this species. Published as part of James G. Mead & Robert L. Brownell, Jr., 1993, Order Cetacea, pp. 349-364 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 361, DOI: 10.5281/zenodo.7352970